THE RELATIONSHIP BETWEEN TRANSFER EXPENDITURES AND PUBLIC FINANCE DEFICIENCIES IN DEVELOPED AND DEVELOPING COUNTRIEIS (Third Sector Social Economic Review, 2022)
After the Second World War, with the changes in the understanding of the state, especially the transfer expenditures increased, but the public income could not be provided to meet this increase. This situation has led to the deterioration of public financial systems in both developed and developing countries. In this study, the relationship between transfer expenditures and public sector financing deficits between 1990 and 2019 in developed and developing countries was examined. In the results of working; Between 1990 and 2019, public deficits and interest expenditures tended to decrease, while subsidies and other transfer expenditures tended to increase in developed countries; In developing countries, on the other hand, while public deficits, subsidies and other transfer expenditures tend to increase, interest expenditures tend to decrease.
Keywords: Public Deficits; Public Expenditures; Transfer Expenditures